Behavior Change Communications During COVID-19 - Melkonyan, Nvard; Melkumyan, Yuliana (YSU Journal of International Affairs, 2022)
This article discusses the behavioral change communications used during COVID-19. The pandemic left its impact not only on people's health, but also on people's lifestyles and daily behavior, creating a "new normal". The concept of "new normal" is used today in the context of COVID-19: what used to be abnormal and unacceptable is now becoming commonplace. Changing the behavioral norms is at the core of fighting the pandemic, which includes building skills, capacity and motivation. Once the barriers to behavior change are identified, it is possible to ensure the desired behavioral change. The scientifically studied behavior change methods include a range of approaches, from education to role modeling. One of the most difficult obstacles to overcome is social stereotypes. The main goals of the behavior change strategy during the COVID-19 pandemic were to contribute to the dissemination of anti-pandemic rules and increase of the vaccination level. In the context of behavioral change communications, experts argued that there is still no clearly proven effective treatment for the coronavirus; the only way to reduce deaths is vaccination. The analysis of measures taken to promote the vaccination process in Armenia shows that some of them were repressive; instead of overcoming stereotypes and reinforcing positive experiences, the vaccination became a means of avoiding economic harm, the emotional context of fear was used instead of positive emotions.
Keywords: behavior change communications; stereotypes; new normal; vaccination; pandemic